PERBEDAAN ANTOMI DAUN PADA TIGA SPESIES TANAMAN BAYAM - Lusiana Kurniawati (JPB - Jurnal Pendidikan Biologi, 2022)
Spinach, whose scientific name is Spinacia oleracea (Amaranthus sp.) Spinach is a C4 plant, which has a unique anatomy, known as kranz anatomy, which is distinctive of C4 plants. This study employs a descriptive methodology. According to the findings of this study, there are variations in the number, average density, and size of sheath cells. The maximum number of bundle sheath cells, 998, was identified in snapper/elephant spinach (A. hybridus L.). The average number of cell density was 63, and there were 148 vascular bundles. The obtained leaf thickness was 234 m, while the cell sizes were between 26 and 39 m. While red spinach (A. amoena Voss.) has the lowest number of bundle sheath cells, 872, the average number of cell density was 62 with 134 vascular bundles. The obtained leaf thickness was 156 m, and the cell sizes were 26 and 39 m. In spinach spines (A. spinosus L.), there are 990 sheath cells with an average cell density of 71 and 132 vascular bundles surrounding it. The obtained leaf thickness was 130 m, and the cell sizes were 26 and 39 m. While the findings on the kranz anatomy of the three spinach species did not reveal any major differences, this is because the kranz morphology is characteristic of C4 plants. The sole distinguishing characteristics are the sheath cells' density and size.